Vegetables in rural Tanzania: Availability and consumer preferences elicited from gendered focus group discussions - Krishna, Vijesh; Sarawathy, Akhil R.; Kangile, Joseph Rajabu; Odjo, Sylvanus; Geetha, Rosalin (CGIAR, 2024)
The diversity of vegetables cultivated and consumed in Tanzania holds immense importance for both nutritional security and cultural heritage (Keller et al. 2005). Vegetables such as African night-shade (Solanum nigrum), amaranths, and jute mallow are not only integral to traditional diets but also offer substantial health benefits, including improved iron levels and joint pain relief.